Pelatihan Kesadaran Wisata Berbasis Sapta Pesona bagi Masyarakat Nagari Sungai Nyalo untuk Mendukung Pariwisata Berkelanjutan - Wedar Pahala Lingga; Eko Purnomo; Asih Gunawiayu (CV. ITTC INDONESIA, 2026)
Sungai Nyalo Village in Pesisir Selatan Regency is one of the leading tourism destinations in West Sumatra with significant natural and cultural tourism potential. However, community awareness of tourism and their role in supporting sustainable destination development remains limited. This community service program aimed to enhance tourism awareness among local residents through Sapta Pesona-based training. The program involved 30 participants consisting of youth groups, tourism business actors, and members of the Tourism Awareness Group (Pokdarwis). The methods employed included lectures, group discussions, service simulations, and evaluations using pre-tests and post-tests. The results indicated a significant improvement in participants’ understanding of tourism awareness, the principles of Sapta Pesona, environmental cleanliness, and hospitality toward visitors. Participants also demonstrated increased commitment to supporting tourism development through community participation and environmental stewardship. This program highlights the importance of continuous capacity-building initiatives to strengthen local community involvement in promoting sustainable tourism development in Sungai Nyalo.